A cowboy's Christmas carol - Harlen, Brenda (Montana mavericks. What happened to Beatrix?, 2020)
Bah, humbug! It's the holiday season in Bronco, but for tour operator Evan Cruise, 'tis only the season for making money. Haunted by his past, he refuses to celebrate the festivities around him -- until he meets Daphne Taylor. As the owner of the local animals sanctuary challenges Evan's resistance to yuletide spirit, their attraction grows into something deeper. But when Daphne uncovers Evan's shocking family secret, it threatens to tear them apart. Will a little Christmas magic change everything?